Short- and long-term dynamics of nutrient removal in floating treatment wetlands. (1st August 2019) - Garcia Chance, Lauren M.; Van Brunt, Sarah C.; Majsztrik, John C.; White, Sarah A.
Abstract: Floating treatment wetlands (FTWs) are a plant-based treatment technology shown to remove excess nutrients and metals from surface waters under a variety of conditions. Plants established in FTWs can accumulate and store nutrients within their tissues, but the amount of uptake and storage is dependent on plant species and nutrient influent concentration. This research was designed to quantify the influence of nutrient load and two plant species on nutrient uptake and partitioning patterns within plant tissues (shoots and roots) so that management recommendations for FTWs can be developed to better protect surface water quality. Treatments consisted of (1) two nutrient loads: a high concentration of 15 mg⋅L −1 nitrogen (N) and a low concentration of 5 mg⋅L −1 N supplied as water soluble fertilizer, and (2) four mesocosm treatments: (a) open water, (b) artificial mat only, no plants, (c) artificial mats planted with Pontederia cordata L., and (d) artificial mats planted with Juncus effusus L.. Plant growth, N, and phosphorus (P) uptake of both P. cordata and J. effusus were greater in the high nutrient treatment than in the low. Pontederia cordata facilitated the highest rates of N (0.31 mg . L . day −1 ) and P (0.34 mg . L . day −1 ) removal. The nutrient removal rates facilitated by Juncus effusus in the high nutrient treatment were much lower for both N (0.03 mg . L . day −1 ) and P (0.02 mg . L . day −1 ). Peak N and P accumulation in J. effusus occurred in September within both root (50 g N and 4.8 g P) and shoot tissues (98 g N and 12.5 g P). The uptake of N and P in P. cordata was highest in root tissues in August (307 g N and 30.5 g P) and in shoot tissues in September (1490 g N and 219.5 g P). In both species, shoots accumulated more N and P than the roots, resulting in a small root:shoot ratio at all stages of the experiment. Harvest of plants from FTWs should occur before plants senesce in the fall, which using P. cordata and J. effusus as model species, occurred from mid- to late-September in USDA Hardiness Zone 8a in the Southeastern United States. Graphical abstract: Image 1 Highlights: Plant N uptake by Pontederia cordata & Juncus effusus was >50% in high treatment. Peak accumulation of nutrients was in August & September. Majority of nutrients accumulated in the shoots tissues rather than the roots. Faster remediation rate over a 7-day period at 15 mg⋅L −1 N compared to 5 mg⋅L −1 N.